Validation of Malay personality taxonomy and development of a work-based personality test using Malay adjectives and Malay lexicons - Maisarah Mohd Taib (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This doctoral research consisted of three major studies concerning psycholexical approach and its application in personality studies. The central focus of this research was on Malay personality factor structure and development of a work-based personality inventory based on this factor structure. Each of the major studies is presented in this thesis as separate chapters (excluding introduction, literature review and conclusion chapters) i.e., Chapter 3 to Chapter 5. Chapter 1 explicated the research background, research questions, importance and significance of the research as well as details on the structure of this doctoral thesis. Chapter 2 presented narrative and systematic reviews of past literature on psycholexically-based personality factor structure studies. The reviews explored findings of personality factor structure across languages and cultures, and presented theoretical as well methodological criticisms that were forwarded as direction for future research. Chapter 3 deliberated re-analysis and refinement of the original adjectival Malay personality taxonomy with the aim to develop a brief indigenous measure of personality, namely, the Malay Personality Adjectives Checklist. Factor analyses confirmed the initial six personality factor structure for the adjectival Malay personality taxonomy. The six factors were labelled as Nefarious, Emotionality, Virtues, Indulgence, eXtraversion and Accommodative (NEVIXA). These six factors were considered emically unique to the Malay with its Emotionality and eXtraversion factors appeared slightly different from the emotionality and extraversion factors of the mainstream Big-5 and Big-6 personality models. The adjectival personality descriptive terms of this factor structure were further examined on their factor loadings for the development and validation of the Malay Personality Adjectives Checklist (MPAC). Analysis using IRT and CTT frameworks showed that MPAC demonstrated sound psychometric properties at both item- and test-levels. Chapter 4 discussed the exploration of Malay personality factor structure using Malay proverbs lexicon in an effort to obtain a comprehensive lexicon for the indigenous Malay personality taxonomy. Factor analyses showed a five-factor proverbial personality taxonomy that are highly similar to the adjectival Malay personality factors, namely, Nefarious, Emotionality, Virtues, eXtraversion and Accommodative. Indulgence factor, however, was not discovered from the Malay proverbs lexicon. Chapter 5 explicated the development and validation of a work-based personality inventory founded on the indigenous Malay personality taxonomy; NEVIXA. The followed the four stages of test development—test conceptualization, test construction, test tryout and item analysis and test validation. The finalized test consisted of 120 items with appropriate discrimination, difficulty and guessing parameter indices. The test also demonstrated appropriate psychometric properties in terms of validity and reliability. The test was named NEVIXA Work-based Personality Inventory (NEVIXA-WPI) and it can be used for work-related applications. In its last chapter, Chapter 6, the thesis discussed the implication of the research as well as limitations, and the thesis forwarded suggestions for future research.